2D a-Fe2O3 doped Ti3C2 MXene composite with enhanced visible light photocatalytic activity for degradation of Rhodamine B. Issue 16 (November 2018) - Zhang, Huoli; Li, Man; Cao, Jianliang; Tang, Qingjie; Kang, Peng; Zhu, Changxin; Ma, Mingjie
Abstract: a-Fe2 O3 /Ti3 C2 MXene composite was synthesized using uniform 2D a-Fe2 O3 nanosheets and layered Ti3 C2 MXene via a facile ultrasonic assisted self-assembly method. The microstructures of as-prepared a-Fe2 O3 /Ti3 C2 MXene composite were characterized and analyzed by X-ray diffraction (XRD), UV–vis diffuse reflectance spectra (UV–vis DRS), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Photocatalytic activity of a-Fe2 O3 /Ti3 C2 MXene composite was evaluated for the degradation of Rhodamine B (RhB) under visible light irradiation. The results indicated that 2D a-Fe2 O3 nanosheets were well dispersed and anchored on the surface of layered Ti3 C2 MXene to form numerous heterostructure interfaces, which can achieve strong visible light absorption and high charge separation efficiency. Due to the synergy effect, a-Fe2 O3 /Ti3 C2 MXene composite had excellent photocatalytic activity and recycling stability. And a possible charge transfer mechanism on the intimate interfaces between a-Fe2 O3 and Ti3 C2 is also proposed.